Distant quasar host galaxies and their environments with multi-wavelength 3D spectroscopy. Issue Volume 15:Issue S359(2020) (March 2019) - Vayner, Andrey
Abstract: We have conducted a multi-wavelength survey of distant (1.3 < z < 2.6) luminous quasars host galaxies using the Keck integral field spectrograph (IFS) OSIRIS and laser guide star adaptive optics (LGS-AO) system, ALMA, HST and VLA. Studying distant quasar host galaxies is essential for understanding the role of active galactic nuclei (AGN) feedback on the interstellar medium (ISM), and its capability of regulating the growth of massive galaxies and their supermassive black holes (SMBH). The combination of LGS-AO and OSIRIS affords the necessary spatial resolution and contrast to disentangle the bright quasar emission from that of its faint host galaxy. We resolve the nebular emission lines, [OIII], [NII], , and [SII] at a sub-kiloparsec resolution to study the distribution, kinematics, and dynamics of the warm-ionized ISM in each quasar host galaxy. The goal of the survey was to search for ionized outflows and relate their spatial extent and energetics to the star-forming properties of the host galaxy. Combining ALMA and OSIRIS, we directly test whether outflows detected with OSIRIS are affecting the molecular ISM. We find that several mechanisms are responsible for driving the outflows within our systems, including radiation pressure in low and high column density environments as well as adiabatic and isothermal shocks driven by the quasar. From line ratio diagnostics, we obtain resolved measurements of the photoionization mechanisms and the gas-phase metallicity. We find that the quasars are responsible for photoionizing the majority of the ISM with metalicities lower than that of gas photoionized by AGN in the low redshift systems. We are now obtaining detailed observations of the circumgalactic medium (CGM) of these systems with the Keck Cosmic Web Imager (KCWI). The gas in the CGM may play an essential role in the evolution of these galaxies.